Cross talk of the immune system in the adipose tissue and the liver in non-alcoholic steatohepatitis: Pathology and beyond - Vonghia, Luisa (World J Hepatol, 2015)
Non-alcoholic steatohepatitis (NASH) is considered to be the hepatic manifestation of the metabolic syndrome, thus has a tight correlation with systemic metabolic impairment. The complex mechanisms underlying the pathogenesis of NASH involve different organs and systems that cross talk together contributing to the onset of NASH. A crucial role is played by inflammatory mediators, especially those deriving from the adipose tissue and the liver, which are involved in the cascade of inflammation, fibrosis and eventually tumorigenesis. In this setting cytokines and adipokines as well as immunity are emerging drivers of the key features of NASH. The immune system participates in this process with disturbances of the cells constituting both the innate and the adaptive immune systems that have been reported in different organs, such as in the liver and in the adipose tissue, in clinical and preclinical studies. The role of the immune system in NASH is increasingly studied, not only because of its contribution to the pathogenetic mechanisms of NASH but also because of the new potential therapeutic options it offers in this setting. Indeed, novel treatments acting on the immune system could offer new options in the management of NASH and the correlated clinical consequences.